[Cu6(NGuaS)6]2+ and its oxidized and reduced derivatives: Confining electrons on a torus - Witte, Matthias; Rohrmüller, Martin; Gerstmann, Uwe; Henkel, Gerald; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)

On-Surface Site-Selective Cyclization of Corrole Radicals - Tebi, Stefano; Paszkiewicz, Mateusz; Aldahhak, Hazem; Allegretti, Francesco; Gonglach, Sabrina; Haas, Michael; Waser, Mario; Deimel, Peter S.; Aguilar, Pablo Casado; Zhang, Yi-Qi; Papageorgiou, Anthoula C.; Duncan, David A.; et al. (ACS Nano)

X-ray Spectroscopy of Thin Film Free-Base Corroles: A Combined Theoretical and Experimental Characterization - Aldahhak, Hazem; Paszkiewicz, M.; Allegretti, F.; Duncan, D. A.; Tebi, S.; Deimel, P. S.; Casado Aguilar, P.; Zhang, Y.-Q.; Papageorgiou, A. C.; Koch, R.; Barth, J. V.; Schmidt, Wolf Gero; et al. (The Journal of Physical Chemistry C)

Electron paramagnetic resonance calculations for hydrogenated Si surfaces - Rohrmüller, M.; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review B)

Tuning the conductivity along atomic chains by selective chemisorption - Edler, F.; Miccoli, I.; Stöckmann, J. P.; Pfnür, H.; Braun, Christian; Neufeld, Sergej; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

Molecular Orbital Rule for Quantum Interference in Weakly Coupled Dimers: Low-Energy Giant Conductivity Switching Induced by Orbital Level Crossing - Nozaki, Daijiro; Lücke, Andreas; Schmidt, Wolf Gero (The Journal of Physical Chemistry Letters)

Understanding band alignments in semiconductor heterostructures: Composition dependence and type-I–type-II transition of natural band offsets in nonpolar zinc-blendeAlxGa1−xN/AlyGa1−yNcomposites - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (Physical Review B)

Optical properties of titanium-doped lithium niobate from time-dependent density-functional theory - Friedrich, Michael; Schmidt, Wolf Gero; Schindlmayr, Arno; Sanna, Simone (Physical Review Materials)
The optical properties of pristine and titanium-doped LiNbO3 are modeled from first principles. The dielectric functions are calculated within time-dependent density-functional theory, and a model long-range contribution is employed for the exchange-correlation kernel in order to account for the electron-hole binding. Our study focuses on the influence of substitutional titanium atoms on lithium sites. We show that an increasing titanium concentration enhances the values of the refractive indices and the reflectivity.

Consistent atomic geometries and electronic structure of five phases of potassium niobate from density-functional theory - Schmidt, Falko; Landmann, Marc; Rauls, Eva; Argiolas, Nicola; Sanna, Simone; Schmidt, Wolf Gero; Schindlmayr, Arno (Advances in Materials Science and Engineering)
We perform a comprehensive theoretical study of the structural and electronic properties of potassium niobate (KNbO3) in the cubic, tetragonal, orthorhombic, monoclinic, and rhombohedral phase, based on density-functional theory. The influence of different parametrizations of the exchange-correlation functional on the investigated properties is analyzed in detail, and the results are compared to available experimental data. We argue that the PBEsol and AM05 generalized gradient approximations as well as the RTPSS meta-generalized gradient approximation yield consistently accurate structural data for both the external and internal degrees of freedom and are overall superior to the local-density approximation or other conventional generalized gradient approximations for the structural characterization of KNbO3. Band-structure calculations using a HSE-type hybrid functional further indicate significant near degeneracies of band-edge states in all phases which are expected to be relevant for the optical response of the material.

Advanced capabilities for materials modelling with Quantum ESPRESSO - Giannozzi, P; Andreussi, O; Brumme, T; Bunau, O; Buongiorno Nardelli, M; Calandra, M; Car, R; Cavazzoni, C; Ceresoli, D; Cococcioni, M; Colonna, N; Carnimeo, I; et al. (Journal of Physics: Condensed Matter)

Creation and Manipulation of Stable Dark Solitons and Vortices in Microcavity Polariton Condensates - Ma, Xuekai; Egorov, Oleg A.; Schumacher, Stefan (Physical Review Letters)

Vortex-vortex control in exciton-polariton condensates - Ma, Xuekai; Schumacher, Stefan (Physical Review B)

Identifying and Realizing Symmetries in Quantum Walks - Symmetry Classes and Quantum Walks - Schütte, Philipp

Physikdidaktische Forschung in der Hochschule. Eine Übersicht über Forschungsdesigns & -methoden - Woitkowski, David; Vogelsang, Christoph (die hochschullehre)

Die Messung fachdidaktischen Wissens bei Anfängern und Fortgeschrittenen im Lehramtsstudiengang Physik - Riese, Josef; Gramzow, Yvonne; Reinhold, Peter (Zeitschrift für Didaktik der Naturwissenschaften)

Two-dimensional switchable blue phase gratings manufactured by nanosphere lithography - Wahle, M.; Brassat, Katharina; Ebel, J.; Bürger, Julius; Lindner, Jörg; Kitzerow, Heinz-Siegfried (Optics Express 25)
Switchable two dimensional liquid crystal diffraction gratings are promising can- didates in beam steering devices, multiplexers and holographic displays. For these areas of applications a high degree of integration in optical systems is much sought-after. In the context of diffraction gratings this means that the angle of diffraction should be rather high, which typically poses a problem as the fabrication of small grating periods is challenging. In this paper, we propose the use of nanosphere lithography (NSL) for the fabrication of two-dimensionally structured electrodes with a periodicity of a few micrometers. NSL is based on the self-assembly of micro- or nanometer sized spheres into monolayers. It allows for easy substrate structuring on wafer scale. The manufactured electrode is combined with a liquid crystalline polymer-stabilized blue phase, which facilitates sub-millisecond electrical switching of the diffraction efficiency at adiffractionangle of 21.4°.

Enhanced columnar mesophase range through distortions in arene cores - Vollbrecht, Joachim; Wiebeler, Christian; Schumacher, Stefan; Bock, Harald; Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals)

Wann ist eine Unterrichtsplanung 'gut'? - Planungsperformanz in Praxisratgebern zur Unterrichtsplanung - Vogelsang, Christoph; Riese, Josef (Die Unterrichtsplanung: Ein in Vergessenheit geratener Kompetenzbereich?! Status Quo und Perspektiven aus Sicht der empirischen Forschung.)

Wie valide sind Professionswissenstests?: Zum Zusammenhang von erfasstem Wissen, Unterrichtshandeln und Unterrichtserfolg - Cauet, Eva; Vogelsang, Christoph (Professionelle Kompetenz von Lehrkräften der Chemie und Physik)

Naturwissenschaftlicher Sachunterricht in der internationalen Vorbereitungsklasse: Sprachliches und fachliches Lernen geflüchteter Kinder fördern – Ein Lehr-Lernprojekt zur sprachsensiblen Entwicklung und Erprobung naturwissenschaftlich-technischen Sachunterrichts in der universitären Ausbildung zukünftiger Sachunterrichtslehrkräfte - Blumberg, Eva; Niederhaus, Constanze (Wie schaffen wir das? Materialien Deutsch als Zweit- und Fremdsprache 97)